The Influence of Audio Podcast in Improving Students’ Interest in Learning English for 7th grade of SMP Bumi Cendekia Yogyakarta - Khusnul Khotimah; Harisna Hikmah (Early Publishing, 2024)
The purpose of this research is to know the effectiveness of podcast in improving students’ interest in learning English. The method is quantitative method, and the design is quasi-experimental. Population of the research is the VII grade of SMP Bumi Cendekia that consists of 43 students. The research used purposive sampling because those classes almost have similar ability in English. VII B as the control class and VII A as the experimental class. The instrument of this research is interest in learning English and it was conducted before and after using the treatment. The result of the data was analyzed using SPSS25. The mean score of control class post-test is 48.86 and the mean score of experimental class posttest is 52.29 Therefore, the result is 3.380>2.020. The meaning is that to > ta (t observation is higher than ta t-table). That means Ho is rejected and Ha is accepted. Based on the data above, the results shows there is an effectiveness of podcast in improving students’ interest in learning English.